Assembly of 809 whole mitochondrial genomes with clinical, imaging, and fluid biomarker phenotyping. Issue 4 (4th January 2018) - Ridge, Perry G.; Wadsworth, Mark E.; Miller, Justin B.; Saykin, Andrew J.; Green, Robert C.; ,; Kauwe, John S.K.
Abstract: Introduction: Mitochondrial genetics are an important but largely neglected area of research in Alzheimer's disease. A major impediment is the lack of data sets. Methods: We used an innovative, rigorous approach, combining several existing tools with our own, to accurately assemble and call variants in 809 whole mitochondrial genomes. Results: To help address this impediment, we prepared a data set that consists of 809 complete and annotated mitochondrial genomes with samples from the Alzheimer's Disease Neuroimaging Initiative. These whole mitochondrial genomes include rich phenotyping, such as clinical, fluid biomarker, and imaging data, all of which is available through the Alzheimer's Disease Neuroimaging Initiative website. Genomes are cleaned, annotated, and prepared for analysis. Discussion: These data provide an important resource for investigating the impact of mitochondrial genetic variation on risk for Alzheimer's disease and other phenotypes that have been measured in the Alzheimer's Disease Neuroimaging Initiative samples.